Adaptive beamforming with 16 element linear array using MaxSIR and MMSE algorithms - Islam, Md. Rafiqul; Hafriz, Fahmy; Norfauzi, Muhammad (IEEE, 2007)
Smart antenna system is a promising technology to provide higher capacity with more reliability. Adaptive beam forming capability is very significant in smart antenna systems. Maximum Signal-to-Interference Ratio (MaxSIR) and Minimum Mean Square Error (MMSE) beamforming algorithms were investigated using 16 elements linear array antenna. Both algorithms were calculated and simulated using Matlab as well as Zeland’s IE3D software. The performance of algorithms for single and multiple beams are presented in this paper.